2013
DOI: 10.1371/journal.pone.0065041
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Psychological Problems in School Settings in Rural Southern Africa

Abstract: BackgroundMany children can be exposed to multiple adversities in low and middle-income countries (LMICs) placing them at potential risk of psychological problems. However, there is a paucity of research using large representative cohorts examining the psychological adjustment of children in school settings in these countries. Children’s psychological adjustment has been shown to affect educational progress which is critical for their future. This study, based in a rural, socio-economically disadvantaged area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Given that no previous psychometric evaluation of the SDQ has taken place in South Africa, the current study therefore aimed to: (i) examine the means, standard deviation, distribution and internal consistency of the SDQ-S in a representative sample of adolescent boys and girls; (ii) compare gender differences in the above psychometric properties; (iii) determine the proportion of boys and girls who scored in the 'normal', 'borderline' and 'abnormal range' of SDQ-S subscales based on UK norms, and, if required, to generate South African cut-off scores; (iv) compare mean SDQ-S scores of the South African sample to previously reported normative data for SDQ-S scores in UK, Australian and Chinese samples; and (v) determine whether the South African SDQ-S data would fit the five-factor structure of the original UK SDQ-S. We hypothesised that significant differences on the basis of gender will exist in SDQ-S scores as found in previous studies (Becker et al 2015;Kremer et al 2015), hypothesised that South African cut-off scores may be required, as reported in other studies from LMICs (Kashala et al 2005;Menon et al 2007;Bakare et al 2010;Cortina et al 2013), and that there would be only partial support for the five-factor structure, as reported elsewhere (Rønning et al 2004;Richter et al 2011;Stevanovic et al 2014). We did not hypothesise any specific patterns of similarities or differences between the South African, UK, Australian and Chinese data, but were keen to explore the crosscountry potential of the instrument.…”
Section: Introductionmentioning
confidence: 90%
“…Given that no previous psychometric evaluation of the SDQ has taken place in South Africa, the current study therefore aimed to: (i) examine the means, standard deviation, distribution and internal consistency of the SDQ-S in a representative sample of adolescent boys and girls; (ii) compare gender differences in the above psychometric properties; (iii) determine the proportion of boys and girls who scored in the 'normal', 'borderline' and 'abnormal range' of SDQ-S subscales based on UK norms, and, if required, to generate South African cut-off scores; (iv) compare mean SDQ-S scores of the South African sample to previously reported normative data for SDQ-S scores in UK, Australian and Chinese samples; and (v) determine whether the South African SDQ-S data would fit the five-factor structure of the original UK SDQ-S. We hypothesised that significant differences on the basis of gender will exist in SDQ-S scores as found in previous studies (Becker et al 2015;Kremer et al 2015), hypothesised that South African cut-off scores may be required, as reported in other studies from LMICs (Kashala et al 2005;Menon et al 2007;Bakare et al 2010;Cortina et al 2013), and that there would be only partial support for the five-factor structure, as reported elsewhere (Rønning et al 2004;Richter et al 2011;Stevanovic et al 2014). We did not hypothesise any specific patterns of similarities or differences between the South African, UK, Australian and Chinese data, but were keen to explore the crosscountry potential of the instrument.…”
Section: Introductionmentioning
confidence: 90%
“…For example, Giarelli and others () found 42 per cent of children in an impoverished rural area screened positive for one or more developmental disabilities. Cortina and others () found teachers identified 41 per cent of children as having behavioural and emotional problems. More conservatively, Flisher and others () estimated the overall prevalence rate of psychiatric disorders at 17 per cent.…”
Section: Relevance Of Dsm Diagnoses To South African Children and Adomentioning
confidence: 98%
“…Around 30 per cent of victims are under 10 years old. Much of the sexual violence occurs in schools; almost a quarter of 10–12‐year‐old rural children feel unsafe in school (Cortina and others, ). In a society where sexual abuse of girls is rampant, gender blind mental disorder statistics may disguise the extent of traumatisation in a group where age and gender may intersect to reproduce them as particular targets for violence and oppression.…”
Section: Risks Affecting the Mental Well‐being Of South African Childmentioning
confidence: 99%
“…As a result, research has shown that programs, like FRIENDS, may not be implemented as effectively or stressed educators are likely to interact with students in ways that undermine the positive effects of delivering the program (Gerber, Whitebook, & Weinstein, 2007;Yoon, 2008). In schools serving students from low socioeconomic backgrounds class sizes are likely to be substantially higher and have more students who exhibit emotional and behavioural difficulties, both of which combine to make teachers' work more challenging and stressful, which may negatively affect the quality of education all the students receive (Cortina et al, 2013). Children and adolescents who come from more socio-economically disadvantaged areas are likely to experience double disadvantage, because not only they are more likely to suffer from emotional difficulties, but they also attend classrooms with teachers who are more stressed and receive less resources (Cortina et al, 2013).…”
Section: Content Of Each Session Sessionmentioning
confidence: 99%
“…In schools serving students from low socioeconomic backgrounds class sizes are likely to be substantially higher and have more students who exhibit emotional and behavioural difficulties, both of which combine to make teachers' work more challenging and stressful, which may negatively affect the quality of education all the students receive (Cortina et al, 2013). Children and adolescents who come from more socio-economically disadvantaged areas are likely to experience double disadvantage, because not only they are more likely to suffer from emotional difficulties, but they also attend classrooms with teachers who are more stressed and receive less resources (Cortina et al, 2013). This has been communicated in a report issued on the status of Australian schools that concluded students from disadvantage backgrounds consistently experience achievement and opportunity gaps when compared to their more privileged peers (Gonski et al, 2011).…”
Section: Content Of Each Session Sessionmentioning
confidence: 99%